EPIDEMIOLOGICAL CHARACTERISTICS OF SALMONELLOSIS IN THE POPULATION OF BELGRADE FOR THE PERIOD 1994-2013 - Maksimovic, Jadranka; Maris, Slavica; Maksimovic, Milos; Nikolic, Aleksandra; Sipetic Grujicic, Sandra (HEALTH CARE, 2022)
Background/Aim: The registered salmonella cases are estimated to constitute 1-10% of the real frequency of this disease. The aim of the research was to analyze epidemiological salmonella characteristics in Belgrade population for the period 1994-2013. Methods: The data on the number of salmonella cases regarding gender, age and municipalities for the given period were taken from the City Institute of Public Health in Belgrade and used to calculate crude, age-specific and standardized incidence rates were used. For estimating the incidence trend joinpoint regression analysis was used. Results: In the given 20-year period there were 12,452 salmonellosis cases, and female infected persons were more present (53.5%) than males (46.5%). In both sexes, the highest average age-specific rates were found in age group 0-4, and the lowest for people age 70 and older. According to joinpoint regression analysis there is a significant incidence decline in men from the age group 15-19 and further on, while in women that decline starts with the age group 10-14. The average standardized salmonellosis incidence rate (per 100,000) was 61.6 (61.7 for men and 61.4 for women). The most frequent Salmonella serotypes isolated from human material were S. enteritidis (81.6%), S. typhimurium (7.7%) and S. infantis (2.6%). Conclusion: The decline in salmonellosis noticed in our study suggests better farming control, better control of meat production and turnover and application of hygienic and sanitary measures in these processes as well as the greater presence of the HACCP standard for the health safety of food in Belgrade.